Dinamika Perbankan Saat Krisis : ROA, LDR, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Perbankan Dengan Pendekatan Stress Test - Izza Fauziah; Ana Kadarningsih (International Forum of Researchers and Lecturers, 2023)
This research aims to determine the effect of ROA, LDR, and company size on company value in banking companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The population taken was banking company semi-annual data for 3 periods totaling 264 data. This research uses a panel data regression analysis method with a stress test approach. The type of stress test used in this research is sensitivity theory, where ROA, LDR, and company size on banking company value show sensitive results when the Covid-19 pandemic shock occurs. In addition, the research results show that ROA, LDR, and company size have a negative and significant effect on company value.